School-level contextual predictors of bullying and harassment experiences among adolescents. (December 2015) - Gower, Amy L.; McMorris, Barbara J.; Eisenberg, Marla E.
Abstract: Background: Bullying and prejudice-based harassment frequently occur in school settings and have significant consequences for the health and wellbeing of young people. Yet far fewer studies have examined the role of the school environment in peer harassment than individual factors. This multilevel study examined associations between a variety of school-level risk and protective factors and student-level reports of bullying and prejudice-based harassment during adolescence. Methods: Data come from 8th, 9th, and 11th graders who completed the 2013 Minnesota Student Survey ( N = 122, 180 students nested in 505 schools). School-level variables were created by aggregating student report data in five areas: academic orientation to school, internal assets, teacher–student relationship quality, feelings of safety at school, and receipt of disciplinary action. Results: Results indicated that youth attending schools with a higher proportion of students with strong internal assets had lower odds of nearly every type of bullying and prejudice-based harassment assessed when compared to youth attending schools with a lower proportion of students with strong internal assets. Additionally, the proportion of students feeling unsafe at school was a fairly consistent risk factor for most types of peer harassment. Conclusion: Findings support the idea that prevention programs aimed at improving school-wide internal assets and feelings of safety at school may be key prevention points. Highlights: Examined school-level risk and protective factors and student-level peer harassment. More students with strong internal assets in a school protects against harassment. More students who feel unsafe at school is a risk factor for peer harassment. School context is a key prevention point.